CRITERIA FOR MENTAL HEALTH IN CHILDREN AND ITS MAINTENANCE (American Journal of Interdisciplinary Research and Development, 2023)
The article describes the criteria for ensuring children's health, the opinions of scientists, and the carried out program works.